Determinan Efektivitas Audit Internal di Inspektorat Provinsi Jawa Timur - Sutaryo, Sutaryo (Jurnal Ilmiah Akuntansi dan Bisnis, 2018)
This effectiveness of internal audit conducted by the Local Government Inspectorate of East Java Province. The purpose of the research conducted is to obtain empirical evidence on the factors that affect the effectiveness of internal audits conducted by the Local Government Inspectorate. The data used in this study comes from questionnaires obtained from 159 respondents. This study, the dependent variable used is the effectiveness of internal audit, while the independent variables used are professional expertise, quality of audit work, career and promotion, support from leadership, and scope of internal audit work. Based on the results of the research note that the quality of audit work, support from the leadership and the scope of internal audit work has a significant influence on the effectiveness of internal audit, while professional and career skills and promotion have no effect on the effectiveness of internal audit in the Local Government Inspectorate of East Java Province. Keywords: Effectiveness of internal audit, professional expertise, quality of audit work, support from leadership, and scope of internal audit work.